Distribution and diversity of polychaetes along a bathyal escarpment in the western Mediterranean Sea. (February 2019) - Langeneck, Joachim; Busoni, Giulio; Aliani, Stefano; Lardicci, Claudio; Castelli, Alberto
Abstract: Knowledge of the diversity of deep-sea polychaetes in the Mediterranean Sea is still scarce and fragmentary, due to the absence of comprehensive taxonomic revisions of several families, with the majority of recent works relying on higher level taxonomy. In the present work samples were collected with a box-corer along the Sardinian Slope, a bathyal escarpment area located in the western Mediterranean Sea, at seven depth levels separated from each other by a 300 m interval, ranging from 600 to 2400 m. Samples were sifted with a 0.3 mm mesh, and polychaetes were identified at the lowest taxonomic level and characterised from the biogeographic and tropho-functional point of view. Ninety-seven taxa were recorded, 60 of which identified at the species level; eight taxa are likely to be undescribed species, possibly endemic to the Mediterranean Sea, whereas another seven are reported for the first time for the Mediterranean Sea. The majority of taxa shows an Atlantic-Mediterranean or strictly Mediterranean distribution, thus confirming the similarity between Atlantic and Mediterranean deep-sea assemblages, but also the unicity of the latter. Conversely, cosmopolitan taxa, usually considered common in deep-sea assemblages, represented a minor component. The trophic guild composition of the assemblage varied along the slope, with shallower assemblages (600–900 m) including a relatively high percentage of predators and microphagous omnivores, while deeper assemblages (1500–1800 m) showed a > 90% percentage of deposit- and filter-feeders, with the 1200 m assemblage characterised by intermediate features. This outcome suggests that in the presently investigated area, the environmental conditions of shallower samples allow the stable occurrence of at least two trophic levels, whereas deeper assemblages depend mainly on organic matter coming from shallower levels and from the water column. The examined polychaete assemblages are characterised by low density and a complete absence of dominance, with the evenness index J' ranging from 0.72 to 1; the wide ranges of the H' index (0.50–2.67) and of Hill's N1 (1.65–14.65) suggest a high variability at low spatial scale. If compared to Atlantic deep-sea polychaete assemblages the assemblage studied shows an almost ten-fold lower organism abundance, but species diversity is only two- to four-fold lower, suggesting that biodiversity in Mediterranean deep-sea environments is possibly underestimated. Diversity of polychaete assemblages in the deep Mediterranean Sea is likely to be underestimated due to their low density, and adequate sampling strategies should be planned to have a better insight into the functioning and diversity of these communities. Highlights: Polychaete diversity and abundance decrease along a bathyal slope (600–2400 m). Several species are new to science and possibly endemic to the Mediterranean Sea. Few cosmopolitan species, most species endemic or Atlantic-Mediterranean. Mediterranean deep-sea polychaetes are largely unknown and worthy of further study.